PENGARUH PUBLIKASI LAPORAN KEUANGAN TERHADAP VOLUME PERDAGANGAN SAHAM - Siti Munfaqiroh (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
Objective of this research the influence of publicizing of financial statement to treade volume of is to study share in Jakarta capital market. This research emphasizes on change of trade volume of share of around date of financial statement publicizing. Research type used by explanatory research. Is used data collecting used purposive sampling. Research sample 16 service firms of (banking) in the year 2004. Data analysis use statistical test with regression method. Result trade indicates the influence of publicizing of financial statement to volume of share in capita! market. This result indicate that financial statement influences trade volume of share of around date of financial statement publicizing. The difference of trade volume of around date of publicizing of financial statement indicate that investor uses financial statement as decision making base. This research support research of Hastuti and Sudibyo (1998), Beza and Na'im (1998), Husnan et al. (1991), and Mardiyah dan Najib (2005).Keywords: financial statement publicizing, share trade volume, parametric, and BEJ